Induction and Regeneration of Autoplasts from Clostridium thermohydrosulfuricum JW102 and Thermoanaerobacter ethanolicus JW200 - Peteranderl, R. (1993)
Autolysis was induced to form stable, cell wall-free cells of Clostridium thermohydrosulfuricum JW102 and Thermoanaerobacter ethanolicus JW200, using a complex medium containing glycine (0.4% wt/vol) and/or sucrose or glycerol (10% wt/vol) at an optimum temperature of 64°C. Autoplasts of both bacteria were grown as L-phase colonies on solid medium; more than 50% of these colonies regenerated to the walled form during prolonged incubation. The removal of the cell wall was confirmed by electron microscopy.